Do you have a complaint? Promoting individual rights in education - Carlbaum, Sara (Scandinavian Journal of Public Administration, 2016)
In this paper, I explore and discuss potential changes in the constructions of citizenship and state-individual relationships in Sweden in reference to increased regulation and the use of formally filed complaints in the Swedish education system. While several studies have examined issues associated with school choice and student influence, few have considered complaints as an aspect of the ‘will to empower’ and the construction of an active citizenship. In this paper, I discuss the motivations behind providing complaint systems via an analysis of official government documents, laws, statutes, reports and web materials. Drawing from citizenship literature and exit/voice theories, the analysis shows that complaints have continuously been reinforced through legislation, regulation and the introduction of Child and School Student Representative (CSSR) for equal rights and Swedish Schools Inspectorate (SSI) via student rights arguments and rule of law mechanisms. Legal discourse, the expansion of law and an increased use of complaints indicate a juridification of politics. This juridification could reinforce individualised perceptions of citizenship and education as a private good that is inherent in school choice and marketisation. An emphasis on student rights and complaints tends to result in contract relationships between the individual and state that risk de-politicising education and motivations for and participation in collective action for a common good.